Seismic reliability and loss assessment of RC frame structures with traditional and innovative masonry infills. (1st April 2020) - Di Trapani, Fabio; Bolis, Valentino; Basone, Francesco; Preti, Marco
Highlights: Innovative vs. traditional infilled RC frame reliability assessment. Explicit modeling of the infill-frame seismic interaction. Discussion of limit states performance for masonry infills. Loss assessment based on site hazard and structural fragility. Reduction of fragility and expected annual loss offered by infills with sliding joints. Abstract: This paper presents a performance-based earthquake engineering framework aimed at the assessment of fragility, reliability and expected annual loss (EAL) of reinforced concrete (RC) frames with traditional infills (TI) and innovative infills with sliding joints (SJ). The main concern is first related to the modification of seismic reliability levels achievable for structural and non-structural limit states by code conforming RC structures when explicitly considering the influence of masonry infills and the quantification of the gain associated with the eventual use of sliding-joint infills (SJI). Further, expected annual losses within the service life are evaluated and compared for the considered structural typologies. The framework is based on the determination of fragility via incremental dynamic analysis (IDA) in order to consider statistical response to input variability. The analyses are carried out on a reference multi-storey multi-bay 2D structure modeled in OpenSEES using a fiber-section approach. Specific structural and non-structural limit states are individuated for the TI and SJI frame structures. Seismic reliability is evaluated by integrating site hazard and structural fragilities resulting for each limit state. Expected annual loss assessment is performed by directly using period dependent hazard curves to determine annual rates of failures associated with limit states. Results show that similar probabilities of exceedance and loss rates are obtained by traditional infill and sliding-joint infill structures at life safety and collapse limit states. On the contrary significant convenience in using SJI is observed for operational and damage limit states in terms of reduced probability of occurrence and EAL.